2014
DOI: 10.1111/jbi.12386
|View full text |Cite
|
Sign up to set email alerts
|

Defining the spatial patterns of historical land use associated with the indigenous societies of eastern North America

Abstract: Aim To review and synthesize multiple lines of evidence that describe the spatial patterns of land use associated with prehistoric and early historical Native American societies in eastern North America in order to better characterize the type, spatial extent and temporal persistence of past land use.Location Temperate forests of eastern North America, and the Eastern Woodlands cultural region.Methods Ethnohistorical accounts, archaeological data, historical land surveys and palaeoecological records describing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 106 publications
(143 reference statements)
5
59
0
Order By: Relevance
“…Nelson 1980;Cronon 1983;Vitebsky 2005). Similarly, pre-industrial anthropogenic landscapes in Eastern United States, display heterogeneous land-use patterns of habited and seemingly uninhabited land (Hammett 1992;Delcourt and Delcourt 2004;Munoz et al 2014). Our findings are also consistent with the demonstrated importance of firewood for people in diverse prehistoric contexts globally (Day 1953;Hastorf et al 2005), while contrasting sharply with the unsustainable historical use of firewood in other ecosystems, e.g.…”
Section: Quantitative Comparisons and Sustainabilitysupporting
confidence: 80%
See 1 more Smart Citation
“…Nelson 1980;Cronon 1983;Vitebsky 2005). Similarly, pre-industrial anthropogenic landscapes in Eastern United States, display heterogeneous land-use patterns of habited and seemingly uninhabited land (Hammett 1992;Delcourt and Delcourt 2004;Munoz et al 2014). Our findings are also consistent with the demonstrated importance of firewood for people in diverse prehistoric contexts globally (Day 1953;Hastorf et al 2005), while contrasting sharply with the unsustainable historical use of firewood in other ecosystems, e.g.…”
Section: Quantitative Comparisons and Sustainabilitysupporting
confidence: 80%
“…Previous studies by Rautio et al (2014), Berg et al (2011) andÖ stlund et al (2013) have shown that harvest levels in some areas exceeded far those in the surrounding landscape. Similarly, Munoz et al (2014), who studied native subsistence strategies in temperate forests of eastern North America, suggested that typical land use patterns resulted in patchworks of managed and unmanaged ecosystems.…”
Section: Sami Migratory Patternsmentioning
confidence: 99%
“…However, much work remains to understand the impact of wildfires and biomass burning emissions on climate, and vice versa (Keywood et al, 2013). Research on human-fire interactions using paleorecords is developing rapidly Perry et al, 2012;McLauchlan et al, 2014;Munoz et al, 2014), but applying insights from paleofire research to fire management and emissions reduction plans remains comparatively limited (Whitlock et al, 2003;Cyr et al, 2009;Coughlan and Petty, 2012;Munoz et al, 2014). By compiling diverse types of paleofire data in a central location and developing opensource analysis tools to explore those data, research can advance more quickly on these topics.…”
Section: Reconstructing Fire History With Sediment-charcoal Datamentioning
confidence: 99%
“…Across the North American continent, Native American societies incorporated into their subsistence economies numerous strategies to increase ecosystem productivity, which had the potential to alter their environments. The use of different strategies by Native American societies varied widely across North America (Doolittle 2002), which produced complex and diverse impacts upon environments (Nowacki et al 2012), even among Native American societies within smaller geographic regions (e.g., New England; Cronon 1983 magnitude of environmental impacts fluctuated over time as Native American societies incorporated different subsistence strategies, and as societies utilized or abandoned resource patches (Munoz et al 2014). The use of different strategies by Native American societies varied widely across North America (Doolittle 2002), which produced complex and diverse impacts upon environments (Nowacki et al 2012), even among Native American societies within smaller geographic regions (e.g., New England; Cronon 1983 magnitude of environmental impacts fluctuated over time as Native American societies incorporated different subsistence strategies, and as societies utilized or abandoned resource patches (Munoz et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous methodological approaches have been applied and synthesized, in order to characterize the spatiotemporal dimensions of Native American impacts (Smith 2011b, Munoz et al 2014. To study impacts upon forest composition, approaches have included the analysis of pollen records (Delcourt et al 1998), soil charcoal records (Fesenmyer and Christensen 2010), dendrochronological records (Ruffner and Abrams 2002), ethnographies (Heidenreich 1972), and presettlement land survey records (PLSRs; Wang 2005).…”
Section: Introductionmentioning
confidence: 99%